BGCS uterine cancer guidelines: Recommendations for practice. (June 2017) - Sundar, Sudha; Balega, Janos; Crosbie, Emma; Drake, Alasdair; Edmondson, Richard; Fotopoulou, Christina; Gallos, Ioannis; Ganesan, Raji; Gupta, Janesh; Johnson, Nick; Kitson, Sarah; Mackintosh, Michelle; et al.
Abstract: The British Gynaecological Cancer Society has issued the first Endometrial (Uterine) Cancer guidelines as recommendation for practice for the UK.